Kikuchi-Fujimoto Disease in a 24-Years Old Saudi Female in Saudi Arabia - Ashour, Abdolrahman; Albeshri, Marwan; Marzouki, Hani; Al-Khayyat, Shadi (Integrative Journal of Medical Sciences, 2018)
Kikuchi-Fujimoto disease (KFD) is a very rare, self-limited and benign inflammatory disorder. It was first reported in Japan in 1972. Diagnosis of Kikuchi disease is confirmed by histopathological investigation of lymph node (LN) biopsy under ultrasound guidance. Computed tomography (CT) and magnetic resonance imaging (MRI) help in the diagnosis of Kikuchi cervical lymphadenopathy but don’t provide a definitive diagnosis. We describe a case of KFD affecting the cervical lymph nodes of a 24-year old Saudi female.